Modulasi pembungaan untuk efisiensi pemuliaan dan optimalisasi biomassa: Tinjauan molekuler dan bioteknologi - Polosoro, Aqwin (Buitenzorg: Journal of Tropical Science, 2025)
Regulation of flowering time is a critical determinant of plant reproductive success and a key trait for optimizing crop adaptation, yield stability, and breeding efficiency. This review highlights recent advances in the molecular pathways controlling flowering, including photoperiod sensing, vernalization and temperature response, autonomous and hormonal regulation, and floral integrator networks. Key genes such as FT, SOC1, FLC, TFL1, and Ghd7 serve as central nodes within these interconnected pathways. The application of genetic engineering tools—including gene overexpression, CRISPR/Cas-mediated knockouts, promoter editing, and transient expression systems—has enabled precise manipulation of flowering phenology across a wide range of crops. These strategies have accelerated fast-track breeding in temperate and tropical perennials and facilitated the enhancement of vegetative biomass in forage and industrial crops through delayed flowering. However, the deployment of flowering-modified genotypes presents challenges, including environmental interactions, phenological trade-offs, biosafety regulation, and potential ecological impacts. Future directions should emphasize the integration of flowering time control with speed breeding platforms, genomic selection, and climate-adaptive trait design, tailored to species—and region—specific requirements. Such multidisciplinary approaches will be vital to advancing crop resilience, productivity, and sustainability under changing environmental conditions.   Keywords: flowering time regulation, genetic engineering, FT gene, fast-track breeding, biomass optimization